Real-time video and force analysis feedback system for learning strength skills on rings in men`s artistic gymnastics - Fujihara, T. (Sports Biomechanics, 2023)
The importance of objective evaluations has gathered more attention than before for a fairer and better performance judgment in gymnastics. The purpose of this report was to disseminate information about our system and provide an example of data utilisation in high-level competitive training from a practical standpoint. The system combined video and force data, measured with two force transducers at the top of the ring cables, wirelessly transmitted to a computer. The force data synchronised with the video were available in real time or immediately after trials, making it possible to objectively quantify the amount of spotting that a gymnast received as external physical assistances. The simplicity of the setup and several special functions of the system led athletes and coaches spontaneously to use it in their regular training to quantify their skill level. Based on the regular utilisation of the system, the general correspondence between objectively measured values and the subjective perception of spotters was determined. In addition, the data suggested the possibility of technical evaluation of a certain type of strength skill based on force data. The data that are shared in this report should be beneficial in facilitating activities to integrate science into practice in gymnastics.